INTERNAL FIXATION OF BOTH BONES FOREARM FRACTURES COMPARISON OF LOCKED COMPRESSION VS LIMITED CONTACT DYNAMIC COMPRESSION PLATES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Background: Forearm function, particularly pronation and supination, depends on the radius's and ulna's connection. Symptoms of malunions might make this joint less effective. Almost of adult forearm fractures including both bones require surgical treatment. Rigid fixation will help restore the natural alignment of the radius and ulna. Patients and Methods: The purpose of this prospective randomized comparative trial was to determine the efficacy of two devices in treating 50 forearm fractures in 25 patients (12 patients with LCP and 13 patients with LC-DCP). Patients having a minimum follow-up of 6 months had an average age of 32 (range: 16–55 years). At the most recent follow-up, the patients' fracture union, function, and complications were evaluated. Results: There was no statistically significant difference in the two groups' grip strength or range of motion. Delay in union was seen in one case (LC-DCP group). One patient in each group had oral antibiotics and supportive care for a superficial wound infection; one patient with LCP had an intravenous antibiotic regimen that effectively cured a deep wound infection and osteomyelitis without the need for further surgery. In conclusion, LCP is an effective tool for treating fractures of the forearm and both bones. Aim of the study: The study was evaluate the efficacy of two compression plate methods for treating diaphyseal fractures in the forearm: locked compression plate (LCP) and limited contact dynamic compression plate (LC-DCP).